1995
DOI: 10.1093/ejo/17.5.403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cranial base and maxillofacial morphology

Abstract: The aims of this study were to investigate the relationships between the cranial base and maxillofacial morphology in Japanese crania, and to examine the differences between Class I and Class II samples. Data were obtained from 46 male Japanese crania from the collection of the Jikei University School of Medicine (Tokyo). The sample represents populations which would have lived during the last 100 years. A principal component analysis of linear and angular measurements showed that the anterior and posterior cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 0 publications
11
43
0
6
Order By: Relevance
“…But these results do not confirm what part of the literature describes about the subject. 1,4,8,9,12,15 This study investigated the differences in the deflection angle of the cranial base, as well as in the length of its anterior (S-N) and posterior (S-Ba) portions in different facial patterns (Pattern I, II and III). However, it is important to keep in mind that the morphogenetic facial pattern is formed by a series of specific characteristics of each face type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But these results do not confirm what part of the literature describes about the subject. 1,4,8,9,12,15 This study investigated the differences in the deflection angle of the cranial base, as well as in the length of its anterior (S-N) and posterior (S-Ba) portions in different facial patterns (Pattern I, II and III). However, it is important to keep in mind that the morphogenetic facial pattern is formed by a series of specific characteristics of each face type.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, any changes that occur between the anterior and posterior cranial base (e.g., changes in the length and angle between them) may generate significant results in the relationships of the facial parts. 15 Ricketts 23 stated that the cranial base has an important influence over the total facial prognathism and the establishment of the jaws anteroposterior relationship. Moyers 21 reported that the growth of the cranial base has a direct effect on the positioning of the mandible and the middle region of the face, and as this base is the most stable of all parts of the craniofacial skeleton, it is less affected by external influences (orthodontic treatment, for example).…”
Section: Introductionmentioning
confidence: 99%
“…The maxillofacial morphology of the specimens was assessed by measurements recorded directly from the skulls and indirectly from standardized radiographs. The radiographic reference points and methods followed closely those defined by Kasai et al [10]. The reference points and variables are defined in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the base of the cranium in the genesis of maxillofacial dysplasias is the subject of an on-going debate [1][2][3][4][5]7,17,[20][21][22][23]29 ; some authors suspect that the base of the cranium is responsible for the development of the anteroposterior dysplasias, because of the much-discussed angle of the base of the cranium as well as for the genesis of the asymmetries being linked to a primary asymmetry of the base of the brain.…”
Section: -3 -Growth Of the Base Of The Craniummentioning
confidence: 99%
“…Certain authors find a relationship linking the shape of the base of the cranium with primarily anteroposterior maxillofacial dysplasia [1][2][3][4][5]7,22,23,29 or asymmetries [14][15][16]19,25,30 .…”
Section: -Introductionmentioning
confidence: 99%